2020
DOI: 10.1007/s00360-020-01296-z
|View full text |Cite|
|
Sign up to set email alerts
|

Short neuropeptide F signaling regulates functioning of male reproductive system in Tenebrio molitor beetle

Abstract: Neuropeptides of short neuropeptides F family (sNPF) have been identified in various arthropods. They are pleiotropic neuromolecules which so far have been mainly associated with regulation of feeding and metabolism, as well as growth and development, locomotion, circadian rhythm or learning and memory. Here, we describe the effects of Tenebrionid sNPF peptide (SGRSPSLRLRFa) on various aspects of the male reproductive physiology in the Tenebrio molitor beetle. We identified in silico the putative sNPF receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…GPCRs are particularly amenable to modulation by small-molecule drugs and therefore have been the targets of about half of the drugs currently used to treat humans [ 19 , 20 ]. Many exceptional studies have revealed how GPCR genes and their potential biological functions can impact insect physiology [ 21 , 22 ], including reproduction [ 23 , 24 , 25 , 26 , 27 , 28 ], regulating growth and development [ 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], the stress response [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], feeding [ 27 , 32 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], behaviors [ 23 , 61 , 62 , 63 , 64 , 65 , 66 ], and other physiological processes [ 46 , 67 , …”
Section: Introductionmentioning
confidence: 99%
“…GPCRs are particularly amenable to modulation by small-molecule drugs and therefore have been the targets of about half of the drugs currently used to treat humans [ 19 , 20 ]. Many exceptional studies have revealed how GPCR genes and their potential biological functions can impact insect physiology [ 21 , 22 ], including reproduction [ 23 , 24 , 25 , 26 , 27 , 28 ], regulating growth and development [ 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], the stress response [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], feeding [ 27 , 32 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], behaviors [ 23 , 61 , 62 , 63 , 64 , 65 , 66 ], and other physiological processes [ 46 , 67 , …”
Section: Introductionmentioning
confidence: 99%
“…In just a few short years, GPCR research in insects has progressed from the initial GPCR gene identification to comprehensive bioinformatics analyses, from single GPCR gene analysis to whole genome sequences of GPCRs and explorations of their pathways, and from traditional transcriptional analysis of the gene expression to gene functional characterization of the GPCR genes in insect physiology and cellular biology. The incredible progress being made in related fields includes a wide range of complementary technologies, including bioinformatics and quantitative expression analyses, with functional studies using RNA interferon revealing potential biological functions that significantly impact insect physiology [ 17 , 18 ], including reproduction [ 19 , 20 , 21 , 22 , 23 , 24 ], regulating growth and development [ 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], the stress response [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], feeding [ 21 , 35 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], general behaviors [ 20 , 57 ,…”
Section: Introductionmentioning
confidence: 99%
“…sNPF levels decreased in diapausing individuals, indicating their role in growth and development [ 23 ]. Short neuropeptide F signaling also inhibited the oviduct muscle contractility, stimulated the contractions of the ejaculatory duct, and regulated the functioning of the male reproductive system in yellow mealworm, Tenebrio molitor [ 24 , 25 , 26 ]. However, there are no reports on the functional roles of sNPF in D. armandi.…”
Section: Introductionmentioning
confidence: 99%